GLP-2 analog teduglutide significantly reduces need for parenteral nutrition and stool frequency in a real-life setting. (August 2018) - Schoeler, Marc; Klag, Thomas; Wendler, Judith; Bernhard, Simon; Adolph, Michael; Kirschniak, Andreas; Goetz, Martin; Malek, Nisar; Wehkamp, Jan
Background: To evaluate the benefits of teduglutide in a real-life setting, we analyzed the data of 14 patients with short bowel syndrome treated with teduglutide. Additionally, we studied glucagon-like peptide 2 (GLP-2) receptor expression in samples of small intestinal and colonic tissue to provide explanations for clinical observations. Methods: Stool frequency and consistency, sensation of thirst, parental calorie or fluid uptake and the number of days on parenteral support per week were collected for up to 2 years. Quantitative real-time polymerase chain reaction of the GLP-2 receptor in healthy controls was performed to better understand clinical response in different patient subgroups. Results: There was a significant reduction in parenteral support after 24 and 48 weeks (by 11.0 and 36.6%, respectively; p < 0.05). Further major improvements were made in several patients after over 1 year (reduction by 79.3%, p < 0.05). The proportion of patients who reduced parenteral support by at least 20% was 33.3%, 54.5% and 71.3% after 24 weeks, 48 weeks and beyond 1 year, respectively. Patients on daily parenteral support showed late but strong amelioration. The reduction of thirst was the earliest marker for response. While stool consistency increased ( p < 0.01), stool frequency decreased ( p < 0.05) significantly after 12 weeks. This reduction was even more pronounced in patients with colon in continuity. Supporting these clinical observations, we found a stronger physiological expression of the GLP-2 receptor in the colon than in the small intestine. Conclusions: Patients benefit from teduglutide in a real-life setting, but in contrast to randomized, controlled studies reduction of parenteral support took longer. We identified early clinical markers of response, such as stool consistency and frequency as well as sensation of thirst. Clinical and molecular observations support the role of the colon as an important target organ of teduglutide.